2017
DOI: 10.21873/anticanres.11574
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoserine Phosphatase Is a Novel Prognostic Biomarker on Chromosome 7 in Colorectal Cancer

Abstract: PSPH could be a novel prognostic biomarker with malignant potential on Ch.7p in CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 5 publications
1
28
0
Order By: Relevance
“…RNA was extracted from frozen tissue specimens and cell lines using ISOGEN-II (Nippon Gene), and RT-quantitative polymerase chain reaction (qPCR) was carried out as previously described. 11 Gene expression was quantified using the follow-…”
Section: Rna Extraction and Reverse Transcriptionquantitative Polymmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was extracted from frozen tissue specimens and cell lines using ISOGEN-II (Nippon Gene), and RT-quantitative polymerase chain reaction (qPCR) was carried out as previously described. 11 Gene expression was quantified using the follow-…”
Section: Rna Extraction and Reverse Transcriptionquantitative Polymmentioning
confidence: 99%
“…Using this screening approach, we previously identified phosphoserine phosphatase (PSPH), located on Ch.7p, as a driver gene in CRC. 11 Herein, we used our screening method and identified DEAD-Box helicase (DDX56), as a candidate oncogene. DDX56 is located on Ch.7p and is a member of the DDX family, known to regulate alternative splicing.…”
mentioning
confidence: 99%
“…We recently established a screening system using a bioinformatics approach with public datasets to identify candidate oncogenes in CRC. Using this system, we identified phosphoserine phosphatase ( PSPH ) and eIF5‐mimic protein 1 ( 5MP1 ) as potential oncogenes on Ch.7p in CRC . Furthermore, we found that their expression was significantly associated with cell cycle progression genes and was an independent poor prognostic factor in patients with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Prognostic factors are needed to identify patients at risk and to optimize treatment. Several factors have been suggested to have an impact on the outcome in terms of survival or locoregional recurrence such as DDR2 expression, phosphoserine phosphatase, preoperative total lesion glycolysis (TLG), nutritional status and lower body mass index (8)(9)(10)(11)(12)(13)(14). These factors can help to understand a patient's prognosis and optimize treatment allocation.…”
mentioning
confidence: 99%